Honduras : Request for a Stand-By Arrangement and an Arrangement Under the Standby Credit Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Honduras. (IMF Staff Country Reports; Country Report ;, 2010)
The economy of Honduras contracted as a result of the global economic crisis. In the economic policy area, the authorities gave priority to strengthening the financial position of the public sector and restarting the external assistance. Measures are taken to strengthen the fiscal position, in particular wage bill control, energy subsidies, public sector tariffs, domestic arrears. Monetary and exchange rate policies will be geared at maintaining low inflation, safeguarding competitiveness, and strengthening the external reserves position. The authorities planned to improve the regulatory framework.